Demonstration of the Capabilities of Transabdominal Ultrasonography in Assessment of Structures and Functional Disorders of Locally Advanced Gastric Cancer of Diverse Localization - Yagubovich Abdullaiev, Rizvan; Victorovna Kryzhanovskaya, Irina; Alekseevich Vinnik, Youri; Narteh Gorleku, Philip (Journal of Digestive Disorders And Diagnosis, 2018)
Introduction: Ultrasound study of locally advanced gastric cancer that has spread to adjoining tissue and lymph nodes. This tumor can be associated with T2 to T4 stages of cancer. A “Locally advanced gastric cancer” is a tumor, which may be categorized as ‘resectable’ cancer when compared with M1 advanced cancer. Objective: The aim of this study was to evaluate the Capabilities of transabdominal ultrasonography in assessment of structures and functional disorders of the locally advanced gastric cancer of diverse localization Materials and Methods: A total of61 patients with locally advanced gastric cancer were analyzed of which 36 (59,0%) were males (mean age 62.7 years) and 25 (41,0%) were females (mean age 59.3 years). All patients were managed surgically and underwent preoperative X-ray, virtual gastroscopy techniques, multidetector computed tomography and transabdominal ultrasonography (USG). Histopathology results found, in 58 (95,1%) cases adenocarcinoma, in 3 (4,9%) – ring-cell carcinoma (cricoidal) gastric cancer was established. Stage T2 was diagnosed in 16 (26.2%) cases, T3 - in 41 (67.2%) cases, T4 - in 4 (6.6%) cases. The stomach tumor in 29 (47.5%) cases was localized mainly in the antrum, 27 (44.3%) – in the body, 5 (8.2%) in the cardia and fundus (Table 1). In 24 (39,3%) cases, pyloric stenos was diagnosed - of which in 6 (9,8%) it was compensated, in 18 (29,5%) - sub compensated. All patients underwent preoperative X-ray, virtual gastroscopy techniques, multidetector computed tomography and transabdominal ultrasonography (USG). Normal ultrasound features were observed in 35 patients without gastric pathology. Ultrasonography was carried out with the convex and micro convex transducers in the frequency range of 2-5 MHz and 4-7 MHz respectively in B and color Doppler modes. Results: The polypoid type of gastric cancer was detected in 3 (4,9±2,8%) cases, the ulcerative type – in 18 (29,5±5,8%), the infiltrative ulcerative type – in 27 (44,3±6,4%) and the diffuse infiltrative type – in 13 (21,3%±5,2%) cases respectively. In 24 (39,3%) cases, pyloric stenos was diagnosed - of which in 6 (9,8%) it was compensated, in 18 (29,5%) – sub compensated. The layers of the gastric wall were not differentiated in all patients with sub compensated pyloric stenos. The gastric wall thickness of the affected area was 10,2±2,9mm in the case compensated pyloric stenosis, the length was 27,1±6,2mm, the diameter of the pylorus was 8,3±0,8mm. Among patients with sub compensated pyloric stenos, the thickness of the gastric wall was 19,8±4,1mm, the length was 43,6±4,5mm, the pyloric diameter was 4,3±1,1mm. Among the 61 patients studied, pathological vascularization was detected in 42 (68.8%) cases. It was observed that, all 4 (6.5%) patients with gastric cancer were stage T4 and 38 (62.3%) were stage T3. Vascularization was weak in 13 cases, in 24 cases - moderate, and in 5 cases - enhanced. Metastases to the regional lymph nodes were diagnosed in 52 cases. Ultrasonographically, they were detected only in 37 (71.2%) cases. Conclusions: In the diagnosis of locally advanced gastric cancer, ultrasonography demonstrates good capabilities for determining the extent and depth of the affected area. Color doppler mode allows the study of vascularisation of a locally thickened area, as well as nearby enlarged lymph nodes, which is very important to ascertain the degree of malignancy of the hyperplastic process. ltrasonography can independently determine the degree of pyloric stenosis in patients with distal gastric cancer.
Keywords: Transabdominal Ultrasonography; Locally Advanced Gastric Cancer; Adenocarcinoma; Histopathology; Lymph Nodes